Study of chemical stability of antivirally active 5-azacytosine acyclic nucleoside phosphonates using NMR spectroscopy - Dracínský, Martin; Krecmerová, Marcela; Holý, Antonín (Bioorganic & medicinal chemistry, 2008)
Hydrolytic decomposition of four 5-azacytosine acyclic nucleoside phosphonates was studied. Products of the decomposition are carbamoylguanidine derivatives. Stability and decomposition products of HPMP-5-azaC (a 5-azacytosine derivative with strong antiviral activity) differ from the other derivatives. The reaction pathway of HPMP-5-azaC involves a formyl derivative formed by intramolecular transformylation reaction.
Keywords: stabilita léku; Antiviral Agents; Nucleosides; Cytosine; magnetická rezonanční spektroskopie; cytosin; organofosfonáty; Magnetic Resonance Spectroscopy; Guanidines; Organophosphonates; guanidiny; hydrolýza; Hydrolysis; antivirové látky; Drug Stability; nukleosidy